2010
DOI: 10.1186/1471-2318-10-79
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of hemodynamic and nutritional parameters between older persons practicing regular physical activity, nonsmokers and ex-smokers

Abstract: BackgroundSedentary lifestyle combined with smoking, contributes to the development of a set of chronic diseases and to accelerating the course of aging. The aim of the study was to compare the hemodynamic and nutritional parameters between elderly persons practicing regular physical activity, nonsmokers and ex-smokers.MethodsThe sample was comprised of 40 elderly people practicing regular physical activity for 12 months, divided into a Nonsmoker Group and an Ex-smoker Group. During a year four trimestrial eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Studies also proved that lifestyle-related behavioural factors might determine healthy ageing. Some of those behavioural aspects include smoking (Chen et al, 2012; Do Nascimento et al, 2015; Francisco et al, 2010; Hussin et al, 2019; Khalili et al, 2014; Leite et al, 2013; Liu et al, 2012; Liu et al, 2011; Ni et al, 2017; Tian et al, 2011; Wang et al, 2013), poly-pharmacy (de Fátima Rosas Marchiori et al, 2015; Wang et al, 2015), nutrition and dietary habits (Fang et al, 2016; Hussin et al, 2019; Lau et al, 2019; Qiu et al, 2012; Sadeghi et al, 2015) personal hygiene practices (Dos Santos et al, 2013; Saengtipbovorn & Taneepanichskul, 2014) and alcohol intake (Liu et al, 2011). Many studies confirmed the role of socioeconomic factors in the determination of healthy ageing (Supplementary Material, Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Studies also proved that lifestyle-related behavioural factors might determine healthy ageing. Some of those behavioural aspects include smoking (Chen et al, 2012; Do Nascimento et al, 2015; Francisco et al, 2010; Hussin et al, 2019; Khalili et al, 2014; Leite et al, 2013; Liu et al, 2012; Liu et al, 2011; Ni et al, 2017; Tian et al, 2011; Wang et al, 2013), poly-pharmacy (de Fátima Rosas Marchiori et al, 2015; Wang et al, 2015), nutrition and dietary habits (Fang et al, 2016; Hussin et al, 2019; Lau et al, 2019; Qiu et al, 2012; Sadeghi et al, 2015) personal hygiene practices (Dos Santos et al, 2013; Saengtipbovorn & Taneepanichskul, 2014) and alcohol intake (Liu et al, 2011). Many studies confirmed the role of socioeconomic factors in the determination of healthy ageing (Supplementary Material, Table 3).…”
Section: Resultsmentioning
confidence: 99%